Front Cover: Preparation of a Stable Bicyclic Aziridinium Ion and Its Ring Expansion toward Piperidines and Azepanes (Asian J. Org. Chem. 9/2017). Issue 9 (28th August 2017) - Choi, Jieun; Yadav, Nagendra Nath; Ha, Hyun‐Joon
Abstract : Expansion pack : A stable form of 1‐azabicyclo[4.1.0]heptane tosylate was synthesized from 2‐[4‐tolenesulfonyloxybutyl]aziridine. Its ring openings with various nucleophiles proceeded in highly regio‐ and stereoselective manners with release of the ring strain by breaking either of the C−N bonds to form a piperidine or an azepane ring. Applying this selective transformation to chiral aziridines led to the asymmetric syntheses of biologically important natural products, such as fagomines, febrifugine, sedamine, hydroxypipercolic acid and balanol. More information can be found in the Full Paper by Hyun‐Joon Ha et al. onpage 1292 in Issue 9, 2017 (DOI:10.1002/ajoc.201700080 ).